1999
DOI: 10.1097/00005537-199904000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Dural Sinus Thrombosis in Childhood

Abstract: CECT with adequate window-level settings allows the diagnosis of a DST with high sensitivity. Treatment of choice for septic DST consists of administration of antibiotics and early surgical drainage. We recommend anticoagulation therapy in children with septic DST during their hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…Neurological deficits were found by deVeber et al (2001) in 38% of the children they studied. Other studies report neurological deficits in 0 to 40% (Barron et al 1992, Medlock et al 1992, Holzmann et al 1999, Lancon et al 1999, deVeber et al 2000, Carvalho et al 2001.…”
Section: Physical Conditionmentioning
confidence: 94%
See 1 more Smart Citation
“…Neurological deficits were found by deVeber et al (2001) in 38% of the children they studied. Other studies report neurological deficits in 0 to 40% (Barron et al 1992, Medlock et al 1992, Holzmann et al 1999, Lancon et al 1999, deVeber et al 2000, Carvalho et al 2001.…”
Section: Physical Conditionmentioning
confidence: 94%
“…A recent study in Canada (deVeber et al 2001) reported an incidence of 0.67 per 100 000 children per year (including neonatal CVST). In children the most frequent causes are regional infections, such as otitis media and mastoiditis, and chronic systemic illnesses (Barron et al 1992;Medlock et al 1992;Holzmann et al 1999;Lancon et al 1999;deVeber et al 2000deVeber et al , 2001Carvalho et al 2001). There is little information about the long-term consequences of CVST, especially on neuropsychological sequelae and quality of life.…”
mentioning
confidence: 99%
“…Single-center and small multicenter series in children 110,378,383,666,668,[679][680][681][682][683][684][685][686][687] have shown that IV UFH and subcutaneous LMWH can be used safely in children. Hemorrhage is uncommon in patients treated with anticoagulants in all series.…”
Section: 48-250 Kawasaki Diseasementioning
confidence: 99%
“…While some of researchers defend routine usage (11,15,18,19), others think that this treatment way will not be efficient (14,16,17). Even some researchers defending the use of oral anticoagulants observed that desired anticoagulant level was not reached in most of patients treated with heparin (20). It was suggested that sigmoid sinus recanalization could be performed without use of oral anticoagulant (17).…”
Section: Discussionmentioning
confidence: 99%